2011
DOI: 10.5551/jat.6437
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Prevents Ischemic Limb Loss in Type 2 Diabetes: Role of p53

Abstract: Aim: Diabetic peripheral artery disease (PAD) is prone to be aggressive and recent reports have demonstrated that p53 accumulation may be responsible for impaired wound healing in diabetes. Statins has been demonstrated to facilitate p53 degradation by activating its specific ubiquitin ligase, MDM2. The aim of this study was to determine whether atorvastatin (ATR) improves the outcome of diabetic PAD through MDM2-mediated reduction of p53. Methods: Male KK/Ay mice (9 weeks old) were treated with ATR (2 mg/kg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 33 publications
4
31
1
Order By: Relevance
“…EPC is already known to promote vascular repair and vasculogenesis, and recent observations support the possibility that pentraxin-3 also possesses atheroprotective 26) and cardioprotective effects 27) , in contrast to other pentraxins, such as C-reactive protein and serum amyloid P. Therefore, increased EPC and pentraxin-3 could possibly play a atheroprotective role, thus correlating with the severity of PAD; however, our study only found that EPC and pentraxin-3 were upregulated in TASC A/B patients, and further studies might be required to reveal the detailed atheroprotective role in PAD, including the various other factors affecting PAD 28,29) . Both SDF-1 and vascular endothelial growth factor attract progenitor cells and are involved in homing, migration and mobilization from bone marrow to peripheral circulation 30,31) , contributing to vascular regeneration.…”
Section: Discussioncontrasting
confidence: 49%
“…EPC is already known to promote vascular repair and vasculogenesis, and recent observations support the possibility that pentraxin-3 also possesses atheroprotective 26) and cardioprotective effects 27) , in contrast to other pentraxins, such as C-reactive protein and serum amyloid P. Therefore, increased EPC and pentraxin-3 could possibly play a atheroprotective role, thus correlating with the severity of PAD; however, our study only found that EPC and pentraxin-3 were upregulated in TASC A/B patients, and further studies might be required to reveal the detailed atheroprotective role in PAD, including the various other factors affecting PAD 28,29) . Both SDF-1 and vascular endothelial growth factor attract progenitor cells and are involved in homing, migration and mobilization from bone marrow to peripheral circulation 30,31) , contributing to vascular regeneration.…”
Section: Discussioncontrasting
confidence: 49%
“…These findings suggested that, in the context of diabetes, p53 might contribute positively to the development of insulin resistance through inducing oxidative stress in skeletal muscle. Consistent with this hypothesis, p53 was found to be an important target to control peripheral artery disease (PAD), which is an ischemic limb syndrome strongly associated with type 2 diabetes (Morimoto, et al 2011). Deferoxamine (DFX), a hypoxia mimetic and iron chelator, was used to mimic PAD in vitro and found to promote p53 accumulation in myoblast cells by suppressing MDM2 expression (Morimoto et al 2011).…”
Section: P53 Regulates Glucose Homeostasis: Glucose Transport Glycolmentioning
confidence: 73%
“…In addition to its roles in diabetes risk and severity, p53 has also been shown to play an active role in these conditions by regulating apoptosis, cell cycle arrest, senescence and inflammation (Gurel, et al 2014; Jazayeri, et al 2008; Morimoto et al 2011; Nguyen, et al 2010; Samarakoon, et al 2012; Zhao, et al 2011). Targeting p53 to treat diabetes potentially offers extra benefits as an inclusive approach to alleviate both diabetes and downstream symptoms.…”
Section: P53 and The Efficacy Of Diabetes Treatmentmentioning
confidence: 99%
“…These findings indicate that apoptosis has a physiologically important role in regulating denervationinduced muscle atrophy (Siu and Always 2005). Likewise, recent reports have implicated p53 accumulation in skeletal muscle for impaired wound healing in diabetic peripheral artery disease (Morimoto et al 2011). These studies are in line with our current findings that showed remarkable P53 gene overexpression levels in tibialis anterior muscles at days 3 and 7 after sciatic crush nerve injury.…”
Section: Discussionmentioning
confidence: 97%